Subjective well-being, life satisfaction and interpersonal relationships associated to socio-demographic and contextual variables - Bedin, Lívia Maria (Applied research in quality of life, 2019)
This study aims associating children’s satisfaction to their interpersonal relationships within their main contexts of interaction (family, friends and school) and their satisfaction regarding their subjective well-being, considering the variables age, gender, type of school (public or private) and city of living (capital or not). There were 2.280 children from 9 to 13 years old (M = 10,99; SD = 0,996), being 1.341 from the capital city (58,8%), most of them from public schools (61%) and 55,5% of the amount were girls. The results showed there is no difference between the average satisfaction data and the interpersonal relationships by age and that children living in country towns are more satisfied with their interpersonal relationships. Children who study in private schools are more satisfied with their family relationships and school environment, while students from public schools are more satisfied with their friendships; besides girls are more satisfied with both their school relationships and friends. The subjective well-being decreased as they become older and boys showed an average subjective well-being significantly higher than girls. Considering the interactions among subjective well-being and the variables evaluated, the children who presented higher average of subjective well-being are those who live in country towns and study in public schools and the ones who live in the capital and study at in private schools